The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1002/jemt.1070270106
|View full text |Cite
|
Sign up to set email alerts
|

A review of electron probe X‐ray microanalysis studies of salivary gland cells

Abstract: Electron probe X-ray microanalysis (EPXMA) has now been successfully applied to several salivary gland preparations. This paper briefly reviews the principles underlying this technique and the specific sample preparation procedures which permit accurate measurement of elemental concentrations in the various intracellular spaces. Findings from salivary gland studies indicate that cytoplasmic and nuclear spaces of nonstimulated acinar cells have high concentrations of K and P, and low concentrations of Mg, Ca, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…3A). Studies on thin sections (Sasaki et al 1983;Izutsu et al 1985Izutsu et al , 1994Izutsu and Johnson 1986) also demonstrated that secretory granules typically have higher concentrationss of Ca, and lower concentrations of P and K than the cytoplasm and nucleus. Also in the apical cytoplasm, the concentrations of these elements decreased (data not shown).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…3A). Studies on thin sections (Sasaki et al 1983;Izutsu et al 1985Izutsu et al , 1994Izutsu and Johnson 1986) also demonstrated that secretory granules typically have higher concentrationss of Ca, and lower concentrations of P and K than the cytoplasm and nucleus. Also in the apical cytoplasm, the concentrations of these elements decreased (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…X-ray microanalysis has been used to study ion distribution in salivary glands under unstimulated and stimulated conditions (Roomans et al 1989;Izutsu et al 1994) and the method has been shown to provide useful information on m o v e m e n t s of ions as a result of stimulation. X-ray microanalysis has been used to study ion distribution in salivary glands under unstimulated and stimulated conditions (Roomans et al 1989;Izutsu et al 1994) and the method has been shown to provide useful information on m o v e m e n t s of ions as a result of stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…acinar/pro-acinar cells, terminal duct cells and serosal demilunes) guanylin immunoreactivity was more widespread within the cells, and, in the submandibular gland, concentrated at the apical side. We observed intense guanylin immunoreactivity at the earliest stages of acinar development, when salivary secretion and ion and fluid transport were defective or minimal (Martinez and Camden 1989;Mork et al 1996;Izutsu et al 1994). In the adult lifetime, this intense activity decreased until it almost disappeared.…”
Section: Discussionmentioning
confidence: 91%
“…This suggests that the limiting membranes are permeable to these ions to the extent that there is a quick equilibration among the various organelles (Gasser et al 1988;Izutsu et al 1994). All the organelles lose K and Cl upon stimulation, including secretory granules.…”
Section: Discussionmentioning
confidence: 99%
“…The ionic mechanisms underlying fluid secretion from rat submandibular glands have been studied using both in vivo (Sasaki et al 1983;Izutsu et al 1994) and in vitro preparations (Martinez andCassity 1983, 1985). The presence of neural tissue and extracellular elements imposing diffusional barriers complicates the interpretation of experimental results in the in vivo preparation, while changes in cells during isolation and differences in the microenviroment in which isolated cells are studied could alter the response to agonists in the in vitro studies.…”
Section: Introductionmentioning
confidence: 99%